Comparative analysis of diisononyl phthalate and di(isononyl)cyclohexane-1,2 dicarboxylate plasticizers in regulation of lipid metabolism in 3T3-L1 cells - BEREKETOĞLU, CEYHUN; TURANLI, BESTE (My University, 2023)
Diisononyl phthalate (DINP) and di(isononyl)cyclohexane-1,2-dicarboxylate (DINCH) are plasticizers introduced to replace previously used phthalate plasticizers in polymeric products. Exposure to DINP and DINCH has been shown to impact lipid metabolism. However, there are limited studies that address the mechanisms of toxicity of these two plasticizers. Here, a comparative toxicity analysis has been performed to evaluate the impacts of DINP and DINCH on 3T3-L1 cells. The preadipocyte 3T3-L1 cells were exposed to 1, 10, and 100 μM of DINP or DINCH for 10 days and assessed for lipid accumulation, gene expression, and protein analysis. Lipid staining showed that higher concentrations of DINP and DINCH can induce adipogenesis. The gene expression analysis demonstrated that both DINP and DINCH could alter the expression of lipid-related genes involved in adipogenesis. DINP and DINCH upregulated Pparγ, Pparα, C/EBPα Fabp4, and Fabp5, while both compounds significantly downregulated Fasn and Gata2. Protein analysis showed that both DINP and DINCH repressed the expression of FASN. Additionally, we analyzed an independent transcriptome dataset encompassing temporal data on lipid differentiation within 3T3-L1 cells. Subsequently, we derived a gene set that accurately portrays significant pathways involved in lipid differentiation, which we subsequently subjected to experimental validation through quantitative polymerase chain reaction. In addition, we extended our analysis to encompass a thorough assessment of the expression profiles of this identical gene set across 40 discrete transcriptome datasets that have linked to diverse pathological conditions to foreseen any potential association with DINP and DINCH exposure. Comparative analysis indicated that DINP could be more effective in regulating lipid metabolism.
Keywords: Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Sosyal ve Beşeri Bilimler; Sosyoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Social Sciences and Humanities; Sociology; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Sosyal Bilimler (SOC); Farmakoloji ve Toksikoloji; Sosyal Bilimler Genel; TOKSİKOLOJİ; ÇEVRE ÇALIŞMALARI; Life Sciences (LIFE); Social Sciences (SOC); PHARMACOLOGY & TOXICOLOGY; SOCIAL SCIENCES, GENERAL; TOXICOLOGY; ENVIRONMENTAL STUDIES; Toksikoloji; Yönetim, İzleme, Politika ve Hukuk; Fizik Bilimleri; Sağlık, Toksikoloji ve Mutajenez; Toxicology; Management, Monitoring, Policy and Law; Physical Sciences; Health, Toxicology and Mutagenesis; disease; fatty acid; gene expression; lipid homeostasis; obesity